Evaluation of Compensation System Based on the Eckenrode Method for Retail Sector's SMEs in Indonesia - Lindawati Kartika; Refindi Rizky Ramadhoni; Silvy Mutiara; Dea Nur Eriza; Andita Sayekti (Universitas Muhammadiyah Jember, 2022)
Small Medium and Entreprises (SMEs) play a major role in the Indonesian economy. The trade sector is the largest, increasing added value by 63.5% compared to the manufacturing sector by 16.7% in 2021. To maintain business continuity, it is important to implement a system of appropriate compensation according to the 3P (Pay for Position, Person, and Performance) principles. Evaluation of the compensation system is important, especially for retail SMEs, where competition for talent and for attracting good human resources is crucial. The purpose of this study was to evaluate the compensation provided by SMEs to employees against the regional minimum wage, develop compensable factors, and evaluate compensation through the eckenrode system to determine the value of points per compensable factor criteria in the SMEs trade sector. This research is a descriptive quantitative study with a sample of 131 employees in six SMEs from Bogor, Depok, Lampung, Bali, and Lombok. The sources of data are secondary data in the form of employee salary surveys and literature studies. Methods of data analysis using the descriptive analysis method and the eckenrode system The results show that there are SMEs that have not implemented a compensation system that meets the regional minimum wage, so it is necessary to determine the new salary structure using ten compensable factors, with education having the highest weight. In the new salary structure, there is an increase in the total salary of 120.04% with a value per salary point of Rp. 17,944. Therefore, the trade sector SMEs can implement the new salary structure in order to improve the welfare of their employees by considering their capitals respectively.